Scientific Nomenclature: What's in a Name? - Jorge Rey (EDIS)
ENY-731, a 5-page illustrated fact sheet by Jorge Rey, explores the practice of using scientific names for plants and animals. He discusses why we need scientific names, the history of scientific nomenclature, "grammar" and what the different parts of a scientific name mean. Includes links to additional references. Published by the UF Department of Entomology and Nematology, June 2006.